Production of Shiga-Toxin by Escherichia coli O157:H7 isolated from Raw Cow Milk obtained within Kaduna Metropolis, Nigeria - Abubakar, S. S.; Maiangwa, J.; Idris, S.; Musa, J. (UMYU Journal of Microbiology Research)
Study’s Excerpt: